Participatory Project Monitoring and Evaluation and Performance of Mango Farming Projects in Makueni County, Kenya - Kisumbi, Charles Kyale; Mulwa, Angeline Sabina; Mbugua, John Mwaura (European Scientific Journal, ESJ, 2022)
This paper focuses on showing the necessity of crafting a feasible project monitoring and evaluation policy which would be an indispensable appraisal tool for assessing the performance of mango projects. It is extracted from the PhD thesis, which aimed to establish the influence of participatory monitoring and evaluation of mango farming projects in Makueni County, Kenya. A pragmatic research paradigm, a descriptive study plan, and a multistage sampling technique were used in the study. A sample of 375 respondents using the Krejcie and Morgan tabulation formula was selected from a population of 12,622 mango farmers. Descriptive and inferential statistics were used as tools for quantitative data analysis, while the content analysis was used for qualitative data analysis. The null hypothesis that there was no significant relationship between the participatory monitoring and evaluation of the project and the performance of the mango farming projects was tested using the correlation and the F-test. The results presented a statistically significant correlation at 95% confidence level with DF (2,367) F=4.756, t=2.269 at level of significance, P=0.000<0.05, r=0.0879 and R square=0.0773. The null hypothesis was therefore rejected, illustrating a significant relationship between the participatory project M&E and the performance of the Mango projects. Based on the results, the study identified a pressing need to use participatory project monitoring and evaluation to address performance issues across the mango value chain. Partnership Support between national and county governments was necessary to engage key experts in the field of agricultural extension, in order to engage mango farmers in improving mango performance.